Plain language summary of the TOPAZ-1 study: durvalumab and chemotherapy for advanced biliary tract cancer - Do-Youn, Oh; Aiwu Ruth, He; Shukui, Qin; Li-Tzong, Chen; Takuji, Okusaka; Arndt, Vogel; Jin Won, Kim; Thatthan, Suksombooncharoen; Myung Ah, Lee; Masayuki, Kitano; Howard, Burris; Mohamed, Bouattour; et al. (Future Oncology, 2023)
This is a summary describing the results of a Phase III study called TOPAZ-1. The study looked at treatment with durvalumab (a type of immunotherapy) and chemotherapy to treat participants with advanced biliary tract cancer (BTC). Advanced BTC is usually diagnosed at late stages of disease, when it cannot be cured by surgery. This study included participants with advanced BTC who had not received previous treatment, or had their cancer come back at least 6 months after receiving treatment or surgery that aimed to cure their disease. Participants received treatment with durvalumab and chemotherapy or placebo and chemotherapy. The aim of this study was to find out if treatment with durvalumab and chemotherapy could increase the length of time that participants with advanced BTC lived, compared with placebo and chemotherapy. Participants who took durvalumab and chemotherapy had a 20% lower chance of experiencing death at any point in the study compared with participants who received placebo and chemotherapy. The side effects experienced by participants were similar across treatment groups, and less than 12% of participants in either treatment group had to stop treatment due to treatment-related side effects. Overall, these results support durvalumab and chemotherapy as a new treatment option for people with advanced BTCs. Based on the results of this study, durvalumab is now approved for the treatment of adults with advanced BTCs in combination with chemotherapy by government organizations in Europe, the United States and several other countries.